Preparedness of Rumah Ilmu Library in Facing Fire Disasters: Safety Education for Campus Society - Dewi, Ayu Fitri; Yasmin, Julia Silverita; Hanan, Latifa; Niha, Nazila Faizatun; Nurrochmah, Siwi Amru (Journal of Safety Education, 2023)
Due to its contents and amenities, Rumah Ilmu, a library building at Universitas Negeri Semarang, is vulnerable to fire disasters. The goal of this study is to analyse the safety aspects of Rumah Ilmu building. In this study, a qualitative methodology and a descriptive strategy were applied and a direct interview with the informants was conducted to collect the data needed. This study was carried out between February and March of 2023. Rumah Ilmu building has met all the government's standards with the fulfilment of 10 components (71.42%), However, 3 components (21.42%) consisting of fire extinguishers, evacuation directions, and assembly points have been implemented but have not met the standards, and 1 component (7.16%) has not been implemented at all, namely the main gate. Suggestions for the preparedness of the Rumah Ilmu in dealing with disasters include increasing the number of fire extinguishers, sprinklers, and rescue facilities, such as installing emergency lighting, adding an area for assembly points, checking periodically related to exit door locking, and arranging an evacuation plan. Additionally, disaster mitigation education should be provided through training, educational videos, and posters to staff and visitors.